Machinability of inconel 718 during face mill - M.S.A., Hafiz; W.N.F., Mohamad; M.S., Kasim; N.S.M., Zainurin; M., Akmal; R., Izamshah; S.B, Mohamed (2018)
In the present study, 8 experiments were conducted in dry cutting and compressed air using full factorial design. The controlled parameters are the cutting speed (20-40 m/min), the feed rate (0.1-0.2 mm/tooth) and the fixed depth of cut (0.1 mm), respectively. The result depicted that the duration of tool life can be extended up 46.3 min with lowest Ra value of 0.8 µm by adopting the compressed air. Besides, the optimum cutting force is 5.32 N.